Attitudes of Tourism Business Actors After the Poso Conflict - Vanda L.A. Pombadju; Angel M. Parirak; Donnye R. Amping; Melda Limaheluw; Sutarto Wijono (Journal of Social Research, 2023)
The indonesian state has so much natural wealth that can be used to support the life of the country and its people, one of the natural wealth owned is in the tourism sector. Poso City as part of Indonesia has so much natural beauty, but the human tragedy that has occurred in Poso, leaves a very dark story, even has an impact on the memory of all Poso people, as well as people outside poso. This impact is obviously traumatizing for the Poso community, the conflict inflicts a deep and lasting trauma even though it has long passed. This research is very important to be carried out in Poso, not only because the issue of tourism is a hot topic for now and its relation to the image of the city of Poso (challenges and opportunities), but also just to bring to the surface the old story of the tragedy that has occurred, which then directs the research to identify the attitudes and traumas of tourism and tourists. But most important in the study is how researchers try to put tourism as a trauma recovery "space" that erodes negative stereotypes and restores the positive image of the city of Poso. The research method used in this study is qualitative with a case study approach and the data collection techniques that will be used in this study are observation, interview, and documentation. The data analysis carried out in this study began with reducing the data from the interview, making it verbatim, and determining the findings of the theme to be chosen for analysis. The purpose of this study was to analyze the attitudes of tourism business actors after the Poso conflict and how they recovered and rose from deep trauma and frustration.